Islamic Educational Policy Analysis on Facilitating Islamic Boarding School Development Under the Local Regulation - Mustofa, Makmur Sofyan; Syukur, Fatah; Muhlisin, Muhlisin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the facilitation of Islamic boarding school (Pesantren) development in Pekalongan City, Indonesia, under the Islamic Boarding School Law No. 18 of 2019 framework. This research analyzes the implementation of Regional Regulation No. 3 of 2022 in implementing this legal framework to support the development of Pesantren, especially in Pekalongan City, Indonesia. This study employs a qualitative approach with a case study design. The case study method was selected as it allows for an in-depth exploration of the implementation of Regional Regulation (Perda) No. 3 of 2022 within the specific context of Pekalongan City, Indonesia, as a locus for pesantren development under the framework of the Islamic Boarding School Law No. 18 of 2019. Data were collected through in-depth interviews with key stakeholders, including Pesantren’s leaders, local government officials, and community members, and analysis of relevant policy documents and reports. This research is based on a Political Knowledge approach to the analysis of policy documents. The analysis technique employed in this study is thematic analysis, which involves identifying, analyzing, and reporting patterns (themes) within qualitative data The important findings of this article show that although national and local regulations provide a strong foundation for the development of Islamic boarding schools, several challenges still exist, including limited funding, uneven distribution of resources, and the need for capacity building among Islamic boarding school administrators. Regional regulations are critical to be issued in order to strengthen central government policies. The study also identifies significant opportunities, such as increased community engagement, improved infrastructure, and increased religious and general education curricula integration. This research contributes to a broader discourse on Islamic education policy by offering insights into implementing national laws at the local level and providing recommendations to optimize the development of Pesantren in Pekalongan City and its surroundings.